Intrathymic somatotropic circuitry: consequences upon thymus involution - Reis, Maria Danielma dos Santos; Veneziani, Luciana Peixoto; Porto, Felipe Lima; Lins, Marvin Paulo; Mendes-da-Cruz, Daniella Arêas; Savino, Wilson (Frontiers in Immunology, 2023)
Growth hormone (GH) is a classic pituitary-derived hormone crucial to body growth and metabolism. In the pituitary gland, GH production is stimulated by GH-releasing hormone and inhibited by somatostatin. GH secretion can also be induced by other peptides, such as ghrelin, which interacts with receptors present in somatotropic cells. It is well established that GH acts directly on target cells or indirectly by stimulating the production of insulin-like growth factors (IGFs), particularly IGF-1. Notably, such somatotropic circuitry is also involved in the development and function of immune cells and organs, including the thymus. Interestingly, GH, IGF-1, ghrelin, and somatostatin are expressed in the thymus in the lymphoid and microenvironmental compartments, where they stimulate the secretion of soluble factors and extracellular matrix molecules involved in the general process of intrathymic T-cell development. Clinical trials in which GH was used to treat immunocompromised patients successfully recovered thymic function. Additionally, there is evidence that the reduction in the function of the somatotropic axis is associated with age-related thymus atrophy. Treatment with GH, IGF-1 or ghrelin can restore thymopoiesis of old animals, thus in keeping with a clinical study showing that treatment with GH, associated with metformin and dehydroepiandrosterone, could induce thymus regeneration in healthy aged individuals. In conclusion, the molecules of the somatotrophic axis can be envisioned as potential therapeutic targets for thymus regeneration in age-related or pathological thymus involution.